2022
DOI: 10.1155/2022/3157986
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Education Combined with Personalized Psychological Nursing Intervention on Pregnancy Outcome of Pregnant Women with Gestational Diabetes Mellitus

Abstract: Objective. To study the effect of health education combined with personalized psychological nursing intervention on pregnancy outcome of pregnant women with gestational diabetes mellitus (GDM). Methods. 170 patients with GDM admitted to Guangdong Women and Children Hospital from January 2018 to December 2018 were selected as study subjects and randomly divided into two groups. During the period from diagnosis of GDM to termination of pregnancy, both groups were given routine education and routine examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…FBG was reported to be significant in six studies (Guo et al, 2019 ; He et al, 2022 ; Rasmussen et al, 2020 ; Rokni et al, 2022 ; Tian et al, 2021 ; Xie et al, 2022 ), while four studies found it significant for the one hour or two-hour postprandial blood glucose assessment (Al-Ofi et al, 2019 ; Guo et al, 2019 ; Kolivand et al, 2019 ; Zandinava et al, 2017 ). While three studies found HbAIc to be significant (Guo et al, 2019 ; Kim et al, 2019 ; Mohebbi et al, 2019 ), another two found it to be not significant but decreased in mean (Al-Ofi et al, 2019 ; Mackillop et al, 2018 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…FBG was reported to be significant in six studies (Guo et al, 2019 ; He et al, 2022 ; Rasmussen et al, 2020 ; Rokni et al, 2022 ; Tian et al, 2021 ; Xie et al, 2022 ), while four studies found it significant for the one hour or two-hour postprandial blood glucose assessment (Al-Ofi et al, 2019 ; Guo et al, 2019 ; Kolivand et al, 2019 ; Zandinava et al, 2017 ). While three studies found HbAIc to be significant (Guo et al, 2019 ; Kim et al, 2019 ; Mohebbi et al, 2019 ), another two found it to be not significant but decreased in mean (Al-Ofi et al, 2019 ; Mackillop et al, 2018 ).…”
Section: Resultsmentioning
confidence: 98%
“…There were twelve randomized control trials (RCT) (Al-Ofi et al, 2019 ; Ammulu et al, 2019 ; Gharachourlo et al, 2018 ; Guo et al, 2019 ; He et al, 2022 ; Johnson & Berry, 2018 ; Kolivand et al, 2019 ; Mackillop et al, 2018 ; Mirghafourvand et al, 2019 ; Rasmussen et al, 2020 ; Tian et al, 2021 ; Xie et al, 2022 ; Zandinava et al, 2017 ), four quasi-experimental (Al-Hashmi et al, 2018 ; Kim et al, 2019 ; Mohebbi et al, 2019 ; Rokni et al, 2022 ), two interpretative phenomenological analysis (IPA) designs (Carolan-Olah et al, 2017b ; Skar et al, 2018 ), and one mixed-methods study (Surendran et al, 2021 ) Only three studies applied theory in their research, and all used the Health Belief Model (Mohebbi et al, 2019 ; Skar et al, 2018 ; Surendran et al, 2021 ). This review identified 2,237 women with GDM (1108 in the intervention group, 1094 in the control group, and 35 in the qualitative).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also very essential to provide nursing staff and midwives with proper and regular up-to-date training and resources to ensure quality diabetes care to the patients during their hospital stay in order to reach a certain level of satisfaction by the patients as well as the staff. In addition, to ensure a better pregnancy outcome in patients with GDM, health education should be mixed with personalized psychological nursing to effectively control patients’ conditions [ 45 , 46 ], which merits widespread promotion. In brief, nurses should further be equipped to tackle high-risk pregnancy conditions including GDM.…”
Section: Introductionmentioning
confidence: 99%